Evolved Standards, Evolving Justices? The Case for a Broader Application of the Eighth Amendment - William W. Berry III (Washington University Law Review, 2018)
In its Eighth Amendment cases, the Supreme Court has often cited counter-majoritarian considerations as the basis for exercising judicial restraint. As a result, excessive and draconian punishments persist in the United States, with the Court being hesitant to use the Constitution to bar state punishment practices. The Court’s evolving standards of decency doctrine, however, is majoritarian. As this Article argues, the doctrinal framework of the Court alleviates the counter-majoritarian difficulty, as the Court’s applications of the Eighth Amendment mirror majoritarian practices and only strike down outlier punishments. Given the lack of justification for judicial restraint under the Eighth Amendment, the Article maps a series of possible applications of the Constitution in this area, both on a micro-level—to limit punishments in certain circumstances—and on a macro-level—to bar certain punishments altogether. In particular, the Article reveals the current ability of the Court to apply its Eighth Amendment doctrine to abolish the death penalty and juvenile life-without-parole sentences. In short, the Article demonstrates that society’s standards with respect to criminal punishments have evolved. The question remains whether the justices themselves will evolve accordingly.
Keywords: Eighth Amendment; counter-majoritarian; Supreme Court; Constitution; Evolving Standards; majoritarianism; JLWOP; LWOP; death penalty; Normative Values; cruel and unusual punishment; constitutional law